2006
DOI: 10.1111/j.1365-277x.2006.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Parent and child reports of fruit and vegetable intakes and related family environmental factors show low levels of agreement

Abstract: The agreement between parent and child reports is weak to moderate and may depend on the age of the child. Fourth graders may overestimate their own intake of fruit and vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
64
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 25 publications
10
64
3
Order By: Relevance
“…These results on food consumption reported by the Chilean children were generally similar to previous studies from other countries that have reported on dietary consumption in 8 to 13 year olds, [12][13][14] although children from this study reported a higher frequency of consumption of produce [8,[15][16][17][18] than some of the previous studies and a slightly higher consumption of snacks and sweets [18] than one previous study. Separating out green and nongreen vegetables in the Chile questionnaire might have increased total vegetable consumption reported by the study children.…”
Section: Study Populationsupporting
confidence: 58%
See 1 more Smart Citation
“…These results on food consumption reported by the Chilean children were generally similar to previous studies from other countries that have reported on dietary consumption in 8 to 13 year olds, [12][13][14] although children from this study reported a higher frequency of consumption of produce [8,[15][16][17][18] than some of the previous studies and a slightly higher consumption of snacks and sweets [18] than one previous study. Separating out green and nongreen vegetables in the Chile questionnaire might have increased total vegetable consumption reported by the study children.…”
Section: Study Populationsupporting
confidence: 58%
“…First, parents may have selected the answers they thought were "correct" rather than accurately recording their true nutrition preferences for their children. This is not likely to be a significant problem since previous studies have found parents to be valid sources in reporting their child's nutritional behaviors [14,15], and are likely to be equally accurate in reporting their own preferences. Second, children could have selected more favorable answers rather than accurately reporting their food consumption.…”
Section: Study Populationmentioning
confidence: 97%
“…The low level of overlap between the two FFQ did not allow us to make a more formal comparison between parental and subject report. Other studies have shown relatively low levels of agreement in younger children (26)(27)(28) . A recent Swedish study reported that 10-12-year-old children generally agreed with their parent's report of their meal patterns but differences were evident regarding the consumption of sweets and chocolate, with the children reporting less frequent consumption (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Parents are determinants of the environment for young children; parent's behaviour has therefore been an obvious area for attention (9)(10)(11)(12) . There are, however, only a few studies assessing child-parent agreement of the determinants of children's food intake, especially their fruit and vegetable intake: a Norwegian study and two Dutch studies (13)(14)(15) . In the Pro Children cross-Europe survey, children and parents were asked parallel questions on the environmental determinants of fruit and vegetable intake, making it possible to study differences in perception.…”
mentioning
confidence: 99%